Effect of maturation conditions on light and temperature requirements during seed germination of Citrullus colocynthis from the Arabian Desert. (19th November 2018) - El‐Keblawy, A.; Soliman, S.; Al‐Khoury, R.; Ghauri, A.; Al Rammah, H.; Hussain, S. E.; Rashid, S.; Manzoor, Z.
Abstract: Seed germination of Citrullus colocynthis, as in many other species of Cucurbitaceae, is inhibited by light, particularly at low temperatures. Germination response to light and temperature has been attributed to day length and temperature during seed maturation. This study assessed the effects of these factors on the germination response of C. colocynthis to temperature and light quality. Ripe fruits were collected from natural habitats during December and February and germinated at three temperatures (15/25, 20/30 and 25/35 °C) in five light treatments (dark, white light and Red:Far Red (R:FR) ratios of 0.30, 0.87 and 1.19). Additionally, unripe fruits were also collected from natural habitats and completed their maturation in growth chambers under different day lengths (6, 16 and 24 h of darkness) at 10/20 °C, and in darkness at both 10/20 °C and 25/35 °C. Mature seeds of the different treatments were germinated in the same five light treatments at 15/25 °C. Germination was significantly higher in the dark than that in any light treatment. Seeds matured at higher temperatures ( i.e . seeds from the December collection and those matured at 25/35 °C) had significantly higher germination than those matured at lower temperatures ( i.e . seeds from the February collection and those matured at 10/20 °C). Dark germination was significantly higher for the December collection than for the February collection. Seeds of the two collections germinated in the dark only at 15/25 °C. However, seeds matured in a growth chamber at 10/20 °C in darkness germinated at 15/25 °C in all light treatments, except for the R:FR ratio 0.30. Seeds of the different treatments failed to germinate in FR‐rich light. This study demonstrates that both temperature and day length during seed maturation play significant roles in the germination response of C. colocynthis . Additionally, the dark requirement for germination is likely beneficial for species with the larger seeds, such as C. colocynthis, which produce bigger seedlings that are able to emerge from deep soils and are competitively superior under dense vegetation and resource‐limited conditions.